Notes to Shakespeare $1 (BVolume 01: Comediess - Johnson, Samuel, 1709-1784; Sherbo, Arthur, 1918-2010 (Salt Lake City, UT : Project Gutenberg, 2005)
"Notes to Shakespeare $1 (BVolume 01: Comedies" by Samuel Johnson is a scholarly commentary on the comedic plays of Shakespeare, likely written during the 18th century. This work serves to provide insights and critical analysis on Shakespeare's comedies, offering readers a deeper understanding of the text, its language, and its historical context within the fabric of English literature. The opening of this volume establishes Johnson's significant contributions to Shakespearean studies, highlighting how his thoughts and nuances often get overshadowed by his more famous preface. It discusses the background of Johnson's editorial work on Shakespeare, the evolution of his commentary, and his unique perspective on the plays. The text introduces Johnson$1 (Bs major ideas, including his interpretations of language, themes, and character intentions, which set the stage for a meticulous examination of works like "The Tempest." He emphasizes that these notes aim not only to clarify textual ambiguities but also to reveal both Shakespeare's artistry and situational context within each play. (This is an automatically generated summary.)s
Augustan Reprint Society, publication number 59-60
Release date is 2005-03-01
Produced by Distributed Proofreaders
Keywords: Shakespeare, William, 1564-1616 -- Criticism and interpretation